45 × ( 2 × x - 4 ) ×13 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(82 - 5.x) : 13 - 4 = 0
(82 - 5.x) : 13 = 0 + 4
(82 - 5.x) : 13 = 4
(82 - 5.x) = 4 . 13
(82 - 5.x) = 52
5.x = 82 - 52
5.x = 30
x = 30 : 5 = 6
(32 . 45) : 2 = (x + 70) : 14 - 40
720 = (x + 70) : 14 - 40
(x + 70) : 14 = 720 + 40
(x + 70) : 14 = 760
(x + 70) = 760 . 14
(x + 70) = 10640
x = 10640 - 70
x = 10570
a) (x – 45).27 = 0 ó x – 45 = 0 ó x = 45
b) 45.(2x – 4).13 = 0 ó 2x – 4 = 0 ó 2x – 4 = 0 ó 2x = 4 ó x = 2
c) (x – 3).(x – 5) = 0
Vậy tập nghiệm của phương trình là S = {3;5}
\(45\left(2x-4\right).13=0\)
\(585\left(2x-4\right)=0\)
\(2x-4=0\)
\(2x=4\)
\(x=2\)
Vậy \(x=2\)
\(45\cdot\left(2x-4\right)\cdot13=0\)
\(45\cdot13\cdot\left(2x-4\right)=0\)
\(585\cdot\left(2x-4\right)=0\)
\(2x-4=0:585=0\)
\(2x=0+4=4\)
\(x=4:2=2\)
45 . ( 2.x - 4 ) . 13 = 0
45 . 13 . ( 2.x - 4 ) = 0
585 . ( 2.x - 4 ) = 0
( 2.x - 4 ) = 0 : 585
2.x - 4 = 0
2.x = 0 + 4
2.x = 4
x = 4 : 2
x = 2
( x + 7 ) . 35 = 2.35
x + 7 = ( 2 . 35 ) : 35
x + 7 = 35
x = 35 - 7
x = 28
43 . ( x - 19 ) = 86
x - 19 = 86 : 43
x - 19 = 2
x = 2 + 19
x = 21
45 x ( 2 x x - 4 ) x 13 =0
45 x ( 2 x x - 4 ) = 0 : 13
45 x ( 2 x x - 4 ) = 0
2 x x - 4 = 0 : 45
2 x x -4 = 0
2 x x = 0 + 4
2 x x = 4
x = 4 : 2
x = 2
45 x ( 2x - 4 ) x 13 = 0
( 2x - 4 ) = 0 : 45 : 13
2x - 4 = 0
2x = 0 + 4
2x = 4
x = 4 : 2
x = 2